DEEPFAKE PORNOGRAFI: STUDI KONSTITUSI DAN PENEGAKANNYA DI INDONESIA - SY., Muhammad Faturrachman (UKM Lembaga Penalaran dan Penulisan Karya Ilmiah Fakultas Hukum Universitas Hasanuddin, 2025)
One of the new patterns emerging in the digital era for perpetrating pornography crimes is the use of deepfake technology. Deepfake pornography, which broadly targets social media users, exploits the vast number of such users in Indonesia and thus calls for the enactment of a dedicated regulation. At present, however, the applicable provisions remain those pre-existing statutes: Law Number 1 of 2024 on the Second Amendment to the Electronic Information and Transactions Law (Law No. 1/2024 on ITE), Law Number 27 of 2022 on Personal Data Protection (Law No. 27/2022 on PDP), Law Number 1 of 2023 on the Criminal Code (Law No. 1/2023 on KUHP), and Law Number 44 of 2008 on Pornography (Law No. 44/2008 on Pornography). The coexistence of multiple statutes capable of criminalizing deepfake pornography offenders paradoxically gives rise to potential legal vacuums or loopholes. This situation necessitates a further, in-depth analysis to uncover the gaps originating from the existing legal framework. Employing a normative-juridical method through legislative and historical approaches and utilizing primary, secondary, and non-legal materials, this study reveals that the current provisions contain loopholes enabling deepfake pornography perpetrators to evade prosecution under pornography offenses. In particular, the exception of pornography intended for personal or private consumption provides a loophole whereby one may use another’s biometric data without satisfying the elements of a pornography offense. Consequently, a specialized regulation is required to address deepfake pornography in Indonesia.